Olympic Opening Ceremonies - Malanski, Daniel, author.
1 online resource (200 pages).
Keywords: This is the first book to unpack the history and significance of the opening ceremony of the Olympic Games, the frontispiece of the most watched event on Earth. Covering the period from the Moscow Olympics in 1980 to Tokyo 2020, the book examines when, how and why the Olympic opening ceremonies' artistic programme became the multi-act spectacles seen today. It argues that the embedded nationalistic, ethnic and environmental discourses contained in opening ceremonies have much to tell us about national narratives, memory and myth-making, about the history of representation, and about how the Olympics and the spectacle of mega-events are prisms through which local and global socio-political issues are refracted, from the climate crisis and the struggle for minority rights to the emergence of a multi-polar world. This book is fascinating reading for anybody with an interest in the sociology, culture, history or politics of sport and events, geopolitics or performance studies.